Voriconazole plasma concentrations in immunocompromised pediatric patients vary by CYP2C19 diplotypes. (June 2014) - Hicks, J Kevin; Crews, Kristine R; Flynn, Patricia; Haidar, Cyrine E; Daniels, Calvin C; Yang, Wenjian; Panetta, John C; Pei, Deqing; Scott, Jeffrey R; Molinelli, Alejandro R; Broeckel, Ulrich; Bhojwani, Deepa; et al.
Aim: Our objective was to describe the association between voriconazole concentrations and CYP2C19 diplotypes in pediatric cancer patients, including children homozygous for the CYP2C19*17 gain-of-function allele.Materials & methods: A linear mixed effect model compared voriconazole dose-corrected trough concentrations (n = 142) among CYP2C19 diplotypes in 33 patients (aged 1–19 years). Voriconazole pharmacokinetics was described by a two-compartment model with Michaelis–Menten elimination.Results: Age (p = 0.05) and CYP2C19 diplotype (p = 0.002) were associated with voriconazole concentrations. CYP2C19*17 homozygotes never attained therapeutic concentrations, and had lower dose-corrected voriconazole concentrations (median 0.01 μg/ml/mg/kg; p = 0.02) than CYP2C19*1 homozygotes (median 0.07 μg/ml/mg/kg). Modeling indicates that higher doses may produce therapeutic concentrations in younger children and in those with a CYP2C19*17/*17 diplotype.Conclusion: Younger age and the presence of CYP2C19 gain-of-function alleles were associated with subtherapeutic voriconazole concentrations. Starting doses based on age and CYP2C19 status could increase the number of patients achieving therapeutic voriconazole exposure. Original submitted 27 November 2013; Revision submitted 13 March 2014